Implementation of Multicultural Education in Islamic Religious Education Subjects at Ciranjang 1 Public High School - Nuri Handayani; Suci Mandhayanti Nurhikmah; Asep Supriyadi (STEBIS Bina Mandiri, 2025)
This study examines the implementation of multicultural education within the Islamic Religious Education (IRE) subject at Ciranjang 1 Public High School. The research aims to analyze how multicultural values are integrated into teaching practices, classroom interactions, and school culture. Using a descriptive qualitative method, data were collected through interviews with teachers and students, classroom observations, and documentation analysis. The findings reveal that multicultural education is implemented through three key strategies: (1) Integrative curriculum design, in which teachers incorporate themes of tolerance, diversity, and inclusivity into lesson plans and learning materials; (2) Student-centered learning, which encourages dialogue, collaborative activities, and reflective discussions that foster mutual respect among students of varied backgrounds; and (3) Supportive school environment, characterized by democratic communication patterns, respect for differences, and school programs that promote cultural harmony. Despite these positive efforts, several challenges persist, including limited teacher training on multicultural pedagogy and insufficient learning resources. Overall, the implementation of multicultural education in IRE classes contributes significantly to shaping students' character, promoting interreligious understanding, and strengthening a harmonious multicultural school climate.